The number of glomeruli and pyruvate metabolism is not strongly coupled in the healthy rat kidney - Bech, Sabrina Kahina; Qi, Haiyun; Mariager, Christian Østergaard; Hansen, Esben Søvsø Szocska; Ilicak, Efe; Zöllner, Frank G.; Laustsen, Christoffer (Magnetic resonance in medicine, 2022)
Purpose The number of glomeruli is different in men and women, as they also present different prevalence and progression of chronic kidney disease. A recent study has demonstrated a potential difference in renal metabolism between sexes, and a potential explanation could be the differences in glomeruli number. This study investigates the potential correlation between glomerular number and pyruvate metabolism in healthy kidneys. Methods This study is an experimental study with rats (N = 12). We used cationized-ferritin MRI to visualize and count glomeruli and hyperpolarized [1-13C]pyruvate to map the metabolism. Dynamic contrast-enhanced MRI was used to analyze kidney hemodynamics using gadolinium tracer. Results Data showed no or subtle correlation between the number of glomeruli and the pyruvate metabolism. Minor differences were observed in the number of glomeruli (female = 24,509 vs. male = 26 350; p = .16), renal plasma flow (female = 606.6 vs. male= 455.7 ml/min/100 g; p = .18), and volume of distribution (female = 87.44 vs. male = 76.61 ml/100 ml; p = .54) between sexes. Mean transit time was significantly prolonged in males compared with females (female = 8.868 s vs. male = 10.63 s; p = .04). Conclusion No strong statistically significant correlation between the number of glomeruli and the pyruvate metabolism was found in healthy rat kidneys.